Methodology of modular design of construction machines. Issue 6 (2nd November 2018) - Zaujec, Pavol; Gulanová, Jana; Gulan, Ladislav
ABSTRACT: This paper describes a method of CAD structural design of modular mobile working machines, especially telescopic excavators. It is mainly focused on the creation of CAD model tree structure and the application of parametric and generative engineering methodology in process of modeling modular construction machines. GRAPHICAL ABSTRACT: